Optimal Phase Number of Induction Motor with the Integrated Frequency Converter - Bugenis, S. J.; Vanagas, J.; Gečys, S. (Elektronika ir Elektrotechnika, 2008)
The analysis of the magnetic field created by a winding connected to the system of non sinusoidal voltages is presented. Windings with number of phases from two to eight are taken into consideration. It is shown, that four-phase and six-phase windings in comparison to the higher harmonics in magnetic field of the induction motor are identical accordingly to two-and three-phase windings. For fivephase and seven-phase windings in some directions the amplitude of the higher harmonic components of magnetic field reduced for the reason that the directions of the magnetic fields created by separate phase windings, are opposite. The corresponding magnetic fields created by them are elliptical or pulsating. Therefore each of them consists of positive and negative sequence components. An exception is only those harmonics, the number of which is aliquot to five for five-phase and to seven for a seven-phase winding. They do not create magnetic fields for the same reason to which magnetic fields do not create the third and aliquot harmonics in a three-phase winding. Therefore, optimum number of phases is three. Ill. 8, bibl. 6 (in English; summaries in English, Russian and Lithuanian).